Molecular structure of Mycobacterium tuberculosis population in Russia and its interaction with neighboring countries. (March 2015) - Mokrousov, I.
Abstract: Background: The tuberculosis (TB) situation in Russia is aggravated by the emergence and the spread of multidrug-resistant strains, HIV co-infection and drawbacks in the health control system. The Mycobacterium tuberculosis population structure in Russia has been defined by the remarkable mass migration in the 20th century, the variable genetic background of different ethnic groups inhabiting Russia, and by the pathobiology of circulating strains. Here, I will review the phylogeography and pathobiology of: (i) the dominating Beijing family; (ii) the Latin-American Mediterranean (LAM) family, the second largest in Russia and MDR-associated in some regions; and (iii) the Ural family, endemic in Russia and thought to be less transmissible and drug resistant. Review and analysis: M. tuberculosis variant Beijing В0/W148 is regarded as a successful clone of M. tuberculosis widespread in the former Soviet Union. However, a closer look reveals a peculiar clinal gradient of its geographic distribution; it peaks in Siberia and, to a lesser extent, in the European part of the former USSR. In contrast, its rate is sharply decreased in the Asian part of the former Soviet Union, and it is absent in the autochthonous populations elsewhere in the world. Two interdependent hypotheses will be put forward. First, B0/W148 likely originated in Siberia and its primary dispersal was driven by a massive population outflow from Siberia to European Russia in the period 1960–1980. Second, a historically recent phylogenetically demonstrated successful dissemination of the Beijing B0/W148 strain was triggered by an advent and wide use of the modern anti-TB drugs and was due to its remarkable capacity to acquire drug resistance. Robust phylogenetic markers were used to study the evolution of LAM and its major sublineages in Russia and its neighboring countries. A total of 250 M. tuberculosis isolates were assigned to LAM based on analysis of LAM-specific SNP in Rv3062 and Rv0129c . The family status was rectified for 121 isolates mis-assigned by spoligotyping to non-LAM families (T1 or T5-RUS1). The re-estimated LAM rate increased twofold in Russia and Kazakhstan and fourfold in Belarus. The majority (>90%) of LAM isolates from all three countries belonged to the LAM-RUS sublineage. In contrast, Ibero-American LAM RD-Rio sublineage was identified in only 7 Russian isolates. These findings and further analysis suggest a monophyletic origin of the LAM-RUS subfamily that is endemic in Russia. In contrast, rare LAM RD-Rio isolates were likely brought to Russia through occasional human contact. The analysis of the Ural family showed its highest prevalence in the North/East Pontic (Black Sea) area that may have been an area of its origin and primary dispersal. Ural family strains are not marked by increased pathogenic capacities, association with drug resistance (although there is a trend towards MDR Ural strains in the European part of the former USSR) or increased transmissibility. This reflects their basically low contagiosity which is why the Ural family is still moderately widespread in central Eurasia. Large-scale SNP or WGS population-based studies targeting strains from indigenous populations and, eventually, analysis of ancient DNA will better test these hypotheses. Host genetics factors likely play the most prominent role in the differential dissemination of particular M. tuberculosis genotypes.